2015
DOI: 10.3996/052013-jfwm-033
|View full text |Cite
|
Sign up to set email alerts
|

Effects of High Salinity Wastewater Discharges on Unionid Mussels in the Allegheny River, Pennsylvania

Abstract: We examined the effect of high salinity wastewater (brine) from oil and natural gas drilling on freshwater mussels in the Allegheny River, Pennsylvania, during 2012. Mussel cages (N = 5 per site) were deployed at two sites upstream and four sites downstream of a brine treatment facility on the Allegheny River. Each cage contained 20 juvenile northern riffleshell mussels Epioblasma torulosa rangiana). Continuous specific conductance and temperature data were recorded by water quality probes deployed at each sit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
34
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(37 citation statements)
references
References 11 publications
(7 reference statements)
3
34
0
Order By: Relevance
“…Wastewater is often high in salinity, toxic trace elements, naturally occurring radioactive materials, and other constituents depending on the producing formation and fluid mix involved in fracturing (Rowan et al 2014, Lauer et al 2016. Exposure to wastewater has been shown to increase plant mortality of terrestrial plants (Adams 2011), reduce juvenile mussel survival rates (Patnode et al 2015), and lower streambed microbial diversity (Akob et al 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Wastewater is often high in salinity, toxic trace elements, naturally occurring radioactive materials, and other constituents depending on the producing formation and fluid mix involved in fracturing (Rowan et al 2014, Lauer et al 2016. Exposure to wastewater has been shown to increase plant mortality of terrestrial plants (Adams 2011), reduce juvenile mussel survival rates (Patnode et al 2015), and lower streambed microbial diversity (Akob et al 2016).…”
Section: Discussionmentioning
confidence: 99%
“…comparison to previous studies. The elevated TDS and Cl concentrations are known to cause high mortality among juvenile freshwater mussels 36 . The chloride concentrations in this study (low dose = 1,240 and high dose late = 4,470 mg/L) fall within the ranges (1,026-5,190 mg/L) used by previous studies to evaluate mortality associated with salinity 34 .…”
Section: Resultsmentioning
confidence: 99%
“…Unionid mussels (Lampsilis Siliquoidea) exposed to elevated salinity in the form of high Cl concentrations from KCl and NaCl salts or synthetic inorganic mixtures that represent produced waters resulted in increased mortality and decreased growth [33][34][35] . In cages placed downstream of an oil and gas discharge, high mortality was observed in riffleshell mussels (Epioblasma torulosa rangiana) 36 . Another study demonstrated that freshwater mussels downstream of produced water discharges incorporated strontium into their shell material with 87 Sr/ 86 Sr signatures similar to that measured in oil and gas wastewaters 37 .…”
mentioning
confidence: 99%
“…Many previous studies have shown that increasing salinity results in the elimination of sensitive taxa and their replacement by eurytopic species (e.g. Williams et al 1990;Boets et al 2012;Kefford et al 2012;Arle and Wagner 2013;Szöcs et al 2014;Patnode et al 2015). Salt-tolerant species including alien species usually become greatly abundant as a result of a lack of competition (an additional effect of a decrease in species richness) and then communities became monospecific (Williams et al 1990;James et al 2003;Carver et al 2009;Bäthe and Coring 2011).…”
Section: Discussionmentioning
confidence: 99%
“…This could be explained by the fact that the subhaline ponds were stocked with the fish that are required for the development of its glochidia and are a good vector for its dispersion (Pip 1986). All of the life stages of unionid mussels are sensitive to an elevated content of chlorides (Bringolf et al 2007), but glochidia are particularly sensitive to acute exposure (Gills 2011; Echols et al 2012;Patnode et al 2015). Beggel and Geist (2015) found that a chloride concentration above 5962 mg L −1 caused the death of A. anatina glochidium in laboratory conditions, whereas according to Canadian Water Quality Guidelines for the Protection of Aquatic Life (2011), the short-term exposures to chloride levels above 640 mg L −1 may pose the greatest toxic effects on glochidia of certain freshwater mussel species (CCME 2011).…”
Section: Discussionmentioning
confidence: 99%